Comparative Effectiveness of Switching to Daptomycin Versus Remaining on Vancomycin Among Patients With Methicillin-resistant Staphylococcus aureus (MRSA) Bloodstream Infections. (29th January 2021) - Schweizer, Marin L; Richardson, Kelly; Vaughan Sarrazin, Mary S; Goto, Michihiko; Livorsi, Daniel J; Nair, Rajeshwari; Alexander, Bruce; Beck, Brice F; Jones, Michael P; Puig-Asensio, Mireia; Suh, Daniel; Ohl, Madeline; et al.
Abstract: Background: Patients with methicillin-resistant Staphylococcus aureus bloodstream infections (MRSA BSI) usually receive initial treatment with vancomycin but may be switched to daptomycin for definitive therapy, especially if treatment failure is suspected. Our objective was to evaluate the effectiveness of switching from vancomycin to daptomycin compared with remaining on vancomycin among patients with MRSA BSI. Methods: Patients admitted to 124 Veterans Affairs Hospitals who experienced MRSA BSI and were treated with vancomycin during 2007–2014 were included. The association between switching to daptomycin and 30-day mortality was assessed using Cox regression models. Separate models were created for switching to daptomycin any time during the first hospitalization and for switching within 3 days of receiving vancomycin. Results: In total, 7411 patients received vancomycin for MRSA BSI. Also, 606 (8.2%) patients switched from vancomycin to daptomycin during the first hospitalization, and 108 (1.5%) switched from vancomycin to daptomycin within 3 days of starting vancomycin. In the multivariable analysis, switching to daptomycin within 3 days was significantly associated with lower 30-day mortality (hazards ratio [HR] = 0.48; 95% confidence interval [CI]: .25, .92). However, switching to daptomycin at any time during the first hospitalization was not significantly associated with 30-day mortality (HR: 0.87; 95% CI: .69, 1.09). Conclusions: Switching to daptomycin within 3 days of initial receipt of vancomycin is associated with lower 30-day mortality among patients with MRSA BSI. This benefit was not seen when the switch occurred later. Future studies should prospectively assess the benefit of early switching from vancomycin to other anti-MRSA antibiotics. Abstract : In a cohort study of patients with methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections admitted to 124 hospitals, there was an association between switch from vancomycin to daptomycin in the first 3 days of treatment and reduced mortality compared with remaining on vancomycin.